Towards new nutritional policies for brain health: A research perspective on future actions - Adan, Roger A.H.; Cirulli, Francesca; Dye, Louise; Higgs, Suzanne; Aarts, Kristien; van der Beek, Eline M.; Buitelaar, Jan K.; Destrebecq, Frédéric; De Witte, Elke; Hartmann, Tobias; Korosi, Aniko; Libuda, Lars; et al. (Brain, Behavior, and Immunity)
Keywords: Behavioral Neuroscience; Endocrine and Autonomic Systems; Immunology

Low leptin levels are associated with elevated physical activity among lean school children in rural Tanzania - Ludwig, Christine; Knoll-Pientka, Nadja; Mwanri, Akwilina; Erfle, Celina; Onywera, Vincent; Tremblay, Mark S.; Bühlmeier, Judith; Luzak, Agnes; Ferland, Maike; Schulz, Holger; Libuda, Lars; Hebebrand, Johannes (BMC Public Health)
Abstract Background In Sub-Saharan African countries, rapid urbanization and increasing socio-economic status are associated with a transition to decreased physical activity (PA). A more sedentary lifestyle is linked to increased body fat leading to increments in leptin levels. Since rodent and human studies in high-income countries have shown that starvation-induced hypoleptinemia triggers high PA, efforts are warranted to pursue the hypothesis that low leptin levels in lean children of low- and middle-income countries (LMIC) are also associated with high PA. Methods In this cross-sectional study, we assessed seven-day PA with triaxial accelerometry (ActiGraph GT3X) among 223 primary school children (9 to 12 years of age) in rural Tanzania. Moderate-to-vigorous PA (MVPA) and total accelerometer counts per day were outcome variables. Leptin was determined using enzyme linked immunosorbent assay tests from dried blood spots. Anthropometric assessments were conducted and food insecurity and socio-demographic data were gathered using semi-structured interviews. Results In this sample of school children in rural Tanzania, leptin concentrations (median: 0.91 ng/mL, P25: 0.55, P75: 1.69), body mass index z-scores (median: -1.35, P25: -1.93, P75: -0.82), and height-for-age-z-scores (median: -1.16, P25: -1.96, P75: -0.61) were low. In contrast, PA levels were high with a median MVPA time of 119 min/day. Linear regression confirmed that leptin levels were negatively associated with MVPA (beta: -18.1; 95%CI: -29.7; -6.5; p = 0.002) and total accelerometer counts (beta: -90,256; 95%CI: -154,146; -26,365; p = 0.006). Children residing in areas with better infrastructure had lower MVPA levels ( p < 0.001) and tended to have higher leptin levels ( p = 0.062) than children residing in areas only reachable via dirt roads. Conclusion Our cross-sectional field study is the first that supports the hypothesis of low leptin levels as a potential endocrine trigger of high PA in lean children of a LMIC. We observed early signs of a PA transition towards a less active lifestyle in a subgroup residing in areas with better infrastructure that concomitantly tended to have higher leptin concentrations. Considering that area-dependent PA differences were more pronounced among girls than boys, whereas differences in leptin levels were less pronounced, not only biological, but also external factors explain PA transition.
Keywords: Public Health; Environmental and Occupational Health

Obesogenic eating behaviour and dietary intake in German children and adolescents: results from the GINIplus and LISA birth cohort studies - Marb, Anne; Libuda, Lars; Standl, Marie; Koletzko, Sibylle; Bauer, Carl-Peter; Schikowski, Tamara; Berdel, Dietrich; von Berg, Andrea; Herberth, Gunda; Bühlmeier, Judith; Harris, Carla P. (European Journal of Clinical Nutrition)
Abstract Background/objectives The transition to adolescence is characterised by considerable behavioural changes, including diet. This study describes the level of obesogenic eating behaviours in 10- and 15-year-olds, and their association with dietary intake. Subjects/methods Participants of the 10- and 15-year follow-ups of the German GINIplus and LISA birth cohort studies were included (N 10 = 2257; N 15 = 1880). Eating behaviours and dietary intake were assessed via self-report questionnaires. Sex-stratified, cross-sectional associations of “external eating”, “emotional eating” and “dietary restraint” (the latter at age 15 years only) with dietary intake (17 food groups—categorised into tertiles, macronutrients, and total energy) were assessed using multinomial logistic or multiple linear regression as required, adjusting for covariates and correcting for multiple testing. Results Reported levels of eating behaviours were low in both age-groups. External eating was higher in 10-year-old males than females, while all eating behaviours were most pronounced in 15-year-old females. At 10 years, emotional eating was associated with medium vegetable intake in females (Relative Risk Ratio (RRR) = 1.84, p = 0.0017). At 15 years, external eating was associated with total energy (kJ) in females ( β = 718, p = 0.0002) and high butter intake in males (RRR = 1.96, p = 0.0019). Dietary restraint in females was inversely associated with total energy ( β = −967, p < 0.0001) and omega-3 fatty acids (Means Ratio (MR) = 0.94, p = 0.0017), and positively associated with high fruit (RRR = 2.20, p = 0.0003) and whole grains (RRR = 1.94, p = 0.0013). Conclusion Obesogenic eating behaviour scores are low among children and adolescents of a predominantly high socioeconomic status population and present only few associations with specific aspects of diet, mainly among adolescent females.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Brief Announcement: Fault-Tolerant Shape Formation in the Amoebot Model - Kostitsyna, Irina; Scheideler, Christian; Warner, Daniel (1st Symposium on Algorithmic Foundations of Dynamic Networks (SAND 2022))

Die Widerständigkeit der Wirklichkeit. Krise in Wolfram Lotzʼ Drama Der große Marsch - Famula, Marta (Theater und Krise. Paradigmen der Störung in Dramentexten und Bühnenkonzepten nach 2000. (= Drama zwischen Text und Bühne 1))

Einleitung - Famula, Marta; Witschel, Verena (Theater und Krise. Paradigmen der Störung in Dramentexten und Bühnenkonzepten nach 2000. (= Drama zwischen Text und Bühne 1))

Die Kunst der Theatereröffnung. Ästhetik und Kulturpoetik von Vorreden und Vorspielen vom 17. Jahrhundert bis heute [in Vorbereitung] (Marta Famula ist Herausgeberin der Schriftenreihe "Drama zwischen Text und Bühne" zus. mit Agata Mirecka und Paul Martin Langner)

Exploring the importance of prior knowledge and verbal cognitive abilities for foreign language learning - Rumlich, Dominik (Cognition and second language acquisition)

Attitudes of German high school students toward different varieties of English - Meer, Philipp; Hartmann, Johanna; Rumlich, Dominik (Applied Linguistics)

Theater und Krise. Paradigmen der Störung in Dramentexten und Bühnenkonzepten nach 2000 (Marta Famula ist Herausgeberin der Schriftenreihe "Drama zwischen Text und Bühne" zus. mit Agata Mirecka und Paul Martin Langner)

Weniger Kompetenz, mehr Resonanz. Contra Position - Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

Software-gestützte Planung der Smart-Service-Transformation - Reinhold, Jannik; Siewert, Michael; Scholtysik, Michel; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Smart Services eröffnen vielfältige Geschäftsmöglichkeiten für produzierende Unternehmen und erfordern zugleich einschneidende Anpassungen ihrer häufig historisch gewachsenen Wertschöpfung. Dieser Beitrag zeigt eine Web-Applikation, die es produzierenden Unternehmen erlaubt, die erforderliche Smart-Service-Transformation zu planen. Dafür werden umfassendes Lösungswissen bereitgestellt und eine individuelle Gestaltungsempfehlungen für die zukünftige Wertschöpfung als Smart-Service-Anbieter gegeben.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Characterization of Usage Data with the Help of Data Classifications - Panzner, Melina; von Enzberg, Sebastian; Meyer, Maurice; Dumitrescu, Roman (Journal of the Knowledge Economy)
Abstract Comprehensive data understanding is a key success driver for data analytics projects. Knowing the characteristics of the data helps a lot in selecting the appropriate data analysis techniques. Especially in data-driven product planning, knowledge about the data is a necessary prerequisite because data of the use phase is very heterogeneous. However, companies often do not have the necessary know-how or time to build up solid data understanding in connection with data analysis. In this paper, we develop a methodology to organize and categorize and thus understand use phase data in a way that makes it accessible to general data analytics workflows, following a design science research approach. We first present a knowledge base that lists typical use phase data from a product planning view. Second, we develop a taxonomy based on standard literature and real data objects, which covers the diversity of the data considered. The taxonomy provides 8 dimensions that support classification of use phase data and allows to capture data characteristics from a data analytics view. Finally, we combine both views by clustering the objects of the knowledge base according to the taxonomy. Each of the resulting clusters covers a typical combination of analytics relevant characteristics occurring in practice. By abstracting from the diversity of use phase data into artifacts with manageable complexity, our approach provides guidance to choose appropriate data analysis and AI techniques.
Keywords: Economics and Econometrics

Business-to-Analytics Canvas - Translation of Product Planning-Related Business Use Cases into Concrete Data Analytics Tasks - Panzner, Melina; Meyer, Maurice; Enzberg, Sebastian von; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Value Creation Framework and Roles for Smart Services - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

To Fix or Not to Fix: A Critical Study of Crypto-misuses in the Wild - Wickert, Anna-Katharina; Baumgärtner, Lars; Schlichtig, Michael; Mezini, Mira
Recent studies have revealed that 87 % to 96 % of the Android apps using cryptographic APIs have a misuse which may cause security vulnerabilities. As previous studies did not conduct a qualitative examination of the validity and severity of the findings, our objective was to understand the findings in more depth. We analyzed a set of 936 open-source Java applications for cryptographic misuses. Our study reveals that 88.10 % of the analyzed applications fail to use cryptographic APIs securely. Through our manual analysis of a random sample, we gained new insights into effective false positives. For example, every fourth misuse of the frequently misused JCA class MessageDigest is an effective false positive due to its occurrence in a non-security context. As we wanted to gain deeper insights into the security implications of these misuses, we created an extensive vulnerability model for cryptographic API misuses. Our model includes previously undiscussed attacks in the context of cryptographic APIs such as DoS attacks. This model reveals that nearly half of the misuses are of high severity, e.g., hard-coded credentials and potential Man-in-the-Middle attacks.

Facharbeiten schreiben - Informationen für Schülerinnen und Schüler - Scharlau, Ingrid; Schreiber, Christine (Psychologieunterricht)

2022 Edsger W. Dijkstra Prize in Distributed Computing - Aguiliera, Marcos; Richa, Andréa W.; Schwarzmann, Alexander A.; Panconesi, Alessandro; Scheideler, Christian; Woelfel, Philipp (PODC ’22: ACM Symposium on Principles of Distributed Computing, Salerno, Italy, July 25 - 29, 2022)

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (1st Conference on Energy, Environment and Digital Transition E2DT)

36th International Symposium on Distributed Computing, DISC 2022, October 25-27, 2022, Augusta, Georgia, USA